Offshore winds obtained from a network of wind‐profiler radars during HyMeX. (1st April 2016) - Saïd, F.; Campistron, B.; Delbarre, H.; Canut, G.; Doerenbecher, A.; Durand, P.; Fourrié, N.; Lambert, D.; Legain, D.
Abstract : 11 ultra‐high‐frequency (UHF) and very‐high‐frequency (VHF) wind‐profiler radars were in operation for 13–18 months during the international Hydrological Cycle in Mediterranean Experiment (HyMeX) field campaign, devoted to the study of the atmospheric and marine water cycle in the western Mediterranean basin. These profilers provided vertical profiles of wind vector, turbulence, precipitation and the height of the atmospheric boundary layer and tropopause. The inland three VHF profilers aimed to document the upstream or downstream synoptic flow conditions. Five UHF profilers for lower atmosphere description were deployed along the French Mediterranean coast and Corsica Island. They were used to retrieve the 3D atmospheric wind fields over the basin, by assuming linearity of the fields inside a limited spatial and temporal domain. The objective of this article is to establish to what extent the 3D wind fields derived from the coastline profiler network are representative of the offshore kinematics. This assessment is performed by comparing more than one year of continuous profiler observations during different weather conditions with balloon radiosoundings and in situ aircraft or boundary‐layer pressurized balloon measurements.